Implikasi Filsafat Pendidikan Esensialisme dalam Pendidikan Akhlak di Perguruan Tinggi (Suatu Tinjauan Teoritis) - Rahmawati; Musthan, Zulkifli; Shaleh, Muh. (Institut Agama Islam Negeri Kendari, 2025)
Moral education in higher education is essential for shaping students' character and ethical awareness. The philosophy of essentialism provides a relevant framework by emphasizing core knowledge and universal values as the foundation for moral development. This article explores the implications of essentialist philosophy in moral education using a library research method. Findings suggest that essentialism-based moral education enhances students' moral sensitivity, ethical reasoning, and social responsibility. Integrating essentialist values into the curriculum creates a supportive environment for character building and increases student engagement in moral learning. It also promotes active participation in social issues and strengthens students’ commitment to ethical behavior. Moreover, this approach supports the development of a positive academic culture through interactive, value-driven learning. In conclusion, essentialism offers a practical and philosophical foundation for advancing moral education in higher education, contributing to the formation of graduates who are not only intellectually capable but also morally grounded and socially conscious.